Building through the flames: Polish-Jewish architects and their networks, 1937–1945 - Roche, Emily (Studia Rossica Posnaniensia, 2024)
Before 1939, Jewish architects were active members of their profession, participating in domestic and international architectural networks and contributing to the built environment of Polish cities. From the mid-1930s, however, intensifying antisemitism and far-right political forces pressured architectural networks to exclude Jews from professional unions. The start of the Second World War and the German occupation in 1939 strained professional architectural networks but led to the formation of underground workshops, cooperatives, and other groups, whose connections extended from Warsaw through the camps and ghettos of occupied Poland. This article presents the history of Jewish-Polish architects from 1937 to 1945. Demonstrating how architectural networks reacted to changing conditions of war, occupation, and genocide, it emphasizes architectural networks as sites of political engagement, ranging from prewar antisemitic attacks on Jews and their removal from the Society of Polish Architects (SARP) to underground architectural networks that hid Jews and allowed them to work. Although the fate of Jewish architects depended largely on their relationships with their professional networks, they also actively decided how to utilize those networks to resist the Nazis and to ensure their survival. This research shows that interpersonal relationships and wartime networks were consequential in determining the wartime fates of Jewish architects and also shaped the profession’s post-war structure.